Nutraceutical activities of aqueous extract of lemon (Citrus lemon Burm) obtained with the extractor Naviglio® - Ferrara, Lydia; Naviglio, Daniele (Progress in Nutrition, 2014)
The lemon extract made with innovative extraction method, the Naviglio extractor® proved with activities for its nutraceutical composition of antioxidants and minerals. Using only distilled water as a extractive liquid has been possible to extract substances with neuroprotective action, for the ability to cross the blood brain barrier without manifesting undesirable side effects. Although the mechanism of action of these substances is not yet known, their use as supplements, could be of great utility in the prevention of neuro-degenerative syndromes.